Sundanese Language and Culture: How Do Sundanese Tertiary Students Deal Both? - Mobit; Retty Isnendes (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2025)
Tertiary undergraduate students take important role to preserve local language. In order to develop local language and culture, they need to consciously aware how they reflect on their attitude on local language and culture. This study examined students’ attitudes toward Sundanese and culture. As college students, it is critical to discover vernacular attitudes, since their advanced education is expected to encourage them to preserve Sundanese language and culture among their surroundings and peers. This study aimed to investigate participants' attitudes toward the Sundanese language and culture in their daily lives, their attempts to conserve them, and the barriers to their preservation. This study used a descriptive mixed method. 46 Sundanese-speaking tertiary students from three universities in West Java participated in the study. Data were collected using Google Form-based questionnaires. The findings indicate that the majority of participants exhibited a high level of sensitivity and understanding of Sundanese language and culture. The participants also engage in revitalizing language through actively involving themselves in various cultural activities. Additionally, participants were conscious on language and culture preservation through participating in a variety of ancient and contemporary cultural activities. In conclusion, the participants still maintain their positive attitude on Sundanese and culture, engage in sociocultural activities and aware toward Sundanese language and culture.